Perceived risk of using online transportation during the COVID-19 pandemic: A MIMIC-model approach - Arlianto Arlianto; Lavenda Geshica (Fakultas Psikologi Universitas Indonesia dan Ikatan Psikologi Sosial-HIMPSI, 2022)
This study aims to assess the construct validity of the perceived risk scale on online transpor-tation users during the COVID-19 outbreak at once to test whether this scale can produce information that is not influenced by individual characteristics using Multiple Indicators and Multiple Cause (MIMIC) models. The 251 participants from different regions in Indonesia, such as East Java, Central Java, West Java, and outside Java participated in this study. The confirmatory factor analysis (CFA) approach was used as the main method in data analysis. The result showed that this six-aspect contextualized version of the scale was fit. The MIMIC model showed that this scale was not influenced by covariate variables, such as age, domicile, sex, marital status, length of time using online transportation, types of online transportation services, and occupation (except private employees). For further research, the exploratory study of risk perception and analysis of the roles of socioeconomic factors are suggested to do.